Mammal seismic line use varies with restoration: Applying habitat restoration to species at risk conservation in a working landscape - Tattersall, Erin R.; Burgar, Joanna M.; Fisher, Jason T.; Burton, A. Cole (Zenodo, 2020)
The data consists of mammal detection data collected from 60 camera trap stations on the east side of the Athabasca River, southwest of Fort McMurray, Alberta, Canada. Between November 2015 - April 2018, we recorded detections for wolves ( Canis lupus ), black bears ( Ursus americanus ), coyotes ( Canis latrans ), Canada lynx (Lynx canadensis), snowshoe hare ( Lepus americanus ), red squirrels ( Tamiasciurus hudsonicus ), moose ( Alces alces ), white-tailed deer ( Odocoileus virginianus ), and woodland caribou ( Rangifer tarandus ). We formatted these data as species detections at each station, as well as species occurrences at the weekly and daily temporal scale. We also used snow presence data from the camera traps, habitat data from the Alberta Vegetation (Alberta Vegetation Interpretation Standards, 2005), and anthropogenic feature data from Alberta Biodiversity Monitoring Institute (abmi.ca). Tattersall et al. (2020) used these data to test hypotheses of species interactions while accounting for effects of snow, habitat, and anthropogenic disturbance. Funding provided by: Alberta Upstream Petroleum Research Fund Crossref Funder Registry ID: Award Number: 19-ERPC-04 Funding provided by: Innotech Alberta Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100020018 Award Number: NXC-107980 Funding provided by: Natural Sciences and Engineering Research Council of Canada Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100000038 Funding provided by: Alberta Upstream Petroleum Research Fund (AUPRF, administered by Crossref Funder Registry ID: Funding provided by: Petroleum Technology Alliance of Canada), oil sands operators, Crossref Funder Registry ID: Funding provided by: University of British Columbia, the Northern Scientific Training Program Crossref Funder Registry ID: